KAJIAN HUKUM TERHADAP KEDUDUKAN ANAK DARI PERKAWINAN SEDARAH DAN SESUSUAN - Suriah Pebriyani Jasmin (IAIN BONE, 2021)
Abstract This research article discusses the legal status of children from inbreeding and milk-sibling marriage. This research is a normative legal research which is oriented towards analysis of applicable legal materials and is related to the status and legal protection of children from inbreeding and milk-sibling marriage. The results showed that the legal status of children from inbreeding and milk-sibling marriage can be legitimate and illegitimate. If the marriage between the two parties (husband and wife) is not known to have a relationship that causes the prohibition of marriage from the beginning, then the status of the children from this marriage (if any) becomes legitimate because it was originally considered legal, although it is found out later that it was forbidden. However, if the marriage is carried out intentionally, the status of the children from inbreeding and milk-sibling marriage will be illegitimate (the children outside marriage).Keywords: Inbreeding;Milk-Sibling Marriage; Status of Children.Abstrak Artikel ini membahas tentang kedudukan hukum anak dari perkawinan sedarah dan sesusuan. Jenis penelitian yang dilakukan ialah penelitian hukum normatif yang berorientasi pada analisis mengenai bahan-bahan hukum yang berlaku dan berkaitan dengan status dan perlindungan hukum anak dari perkawinan sedarah dan sesusuan.Hasil dari penelitian menunjukkan bahwa status hukum anak dari perkawinan sedarah dan sesusuan dapat menjadi sah dan tidak sah. Apabila perkawinan di antara kedua belah pihak (suami-istri) sejak awal tidak diketahui memiliki hubungan yang menyebabkan keharaman perkawinan, maka status anak dari perkawinan tersebut (jika ada) menjadi sah, sebab perkawinan tersebut semula dianggap sah, meskipun di kemudian hari diketahui keharaman perkawinan di antara keduanya. Akan tetapi jika perkawinan tersebut dilakukan secara sengaja, maka status anak dari perkawinan sedarah dan sesusuan menjadi tidak sah (anak luar kawin).Kata Kunci: Sesusuan;Perkawinan sedarah; Kedudukan anak.